Application of 3D Laser Scanning in Underground Station Cavity Clusters - Li Pinpin; Qiu Wenge; Cheng Yunjian; Lu Feng (Advances in Civil Engineering)
Given the shortcomings of the tunnel overbreak and underbreak control and primary support sectional area detection such as the single means, large workload, low efficiency, and poor accuracy, the use of three-dimensional laser technology can solve the above problems. Based on the Badaling Tunnel Great Wall underground station of the Beijing-Zhangjiakou Railway, the 3D laser scanning technology is used to analyze the distribution of the tunnel overbreak and underbreak and the sectional area of the primary support, compared with the total station measurement results. The results showed that the layout of the scanning measurement station should consider the requirements of scanning accuracy, control the station length and scanning incidence angle, and minimize the scanning station length to reduce the scanning error. The majority of the tunnel section was in overbreak, with the overbreak area ranging from 6.22 m2 to 13.17 m2and the overbreak rate ranging from 0.283 to 0.598, and the area of underbreak was relatively small; no overexceeded headroom was found in the primary support, and the tunnel vault was not overbreak. The primary support clearance value of the vault is 0∼15 mm, the clearance value of the sidewall is 35 mm∼40 mm, and the sidewall needs to be secondary shotcrete. The difference value between the 3D laser scanning measurement data and the total station measurement data is within 3 mm, which is within the error range, indicating the validity and reliability of the 3D laser measurement result.